1998
DOI: 10.1159/000011907
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dose Intensity in Conservative Treatment ofAnal Canal Carcinoma

Abstract: Chemoradiotherapy (CRT) is considered the standard treatment for anal canal cancer. However, the optimum schedule of therapy has yet to be defined. This study was carried out to evaluate the role of dose intensity (DI) of chemotherapy (ChT) and radiotherapy (RT) on the outcome of patients submitted to CRT. Thirty-five consecutive patients with anal canal carcinoma received a combination of RT (median dose 56 Gy) and ChT (two or more cycles of 5-fluorouracil and mitomycin C). With a median follow-up of 33 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…Allal et al [22]reported the results of a univariate analysis showing the significant influence of an OTT longer than 75 days – nearly twofold to the OTT in our series – on local control in a series of 137 patients with T2–T3 tumors. Similar results were achieved in the series of Ceresoli et al [23], where a treatment time of more than 70 days was correlated with a worse disease-free survival only by univariate analysis. In the study of Ngan et al [24]on 96 patients, the actuarial disease-free survival was 66% after 5 years for patients without treatment interruption and 54% for patients with an interruption of treatment, but no quantitative analyses concerning OTT was performed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Allal et al [22]reported the results of a univariate analysis showing the significant influence of an OTT longer than 75 days – nearly twofold to the OTT in our series – on local control in a series of 137 patients with T2–T3 tumors. Similar results were achieved in the series of Ceresoli et al [23], where a treatment time of more than 70 days was correlated with a worse disease-free survival only by univariate analysis. In the study of Ngan et al [24]on 96 patients, the actuarial disease-free survival was 66% after 5 years for patients without treatment interruption and 54% for patients with an interruption of treatment, but no quantitative analyses concerning OTT was performed.…”
Section: Discussionsupporting
confidence: 89%
“…Another point of criticism may be that our analyses mainly focus on the radiotherapeutic features of the combined modality treatment, although the time dependence of an RCT also depends on the particular chemotherapy schedule involved. However, even though attempts have been made to quantify the dose intensity of chemotherapy in the scope of RCT for anal cancer [23], it is difficult to estimate the antitumoral effects of the chemotherapy, which can in particular mask the effects of treatment interruptions.…”
Section: Discussionmentioning
confidence: 99%
“…At MD Anderson, local control was 50% for all stages receiving 45-49 Gy and 90% for those patients receiving greater than or equal to 55 Gy [7] . Overall treatment time has similarly been shown to impact outcome in treatment of anal cancer [10][11][12][13][14][15] . In the second phase of the dose escalation study RTOG 9208 without the mandatory break, the 1-year colostomy rate decreased from 23% to 11% [10,14] .…”
Section: Discussionmentioning
confidence: 99%
“…Built in breaks > 37.5 d correlate with poorer loco-regional control in patients treated with a median of 40 Gy to the pelvis and a 20 Gy boost with either external beam radiation or brachytherapy [15] . Ceresoli et al [13] found that overall treatment times longer than 70 d were related to a worse disease-free survival in a group of patients treated with a median radiation dose of 56 Gy. Overall treatment times > 75 d were associated with poorer local control (69% vs 85%) in a study by Allal [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the length of treatment interruption before application of the boost either by brachytherapy or external beam radiation, Peiffert et al observed a decreased local control if the gap exceeded 63 days [15] and Weber et al [16] and Deniaud-Alexandre et al [7] showed an association with improved outcome in patients treated with a gap shorter than 38 days. When considering the overall treatment time Ceresoli et al found an inferior disease-free survival in patients with an overall treatment time exceeding 70 days [17]. Allal et al found a poorer local control rate if the overall treatment time exceeded 75 days [18].…”
Section: Discussionmentioning
confidence: 99%